Value Creation along a Production-Service Value Chain - Gerse-Krizsa, Teréz; Kalló, Noémi (International Journal of Engineering and Management Sciences, 2022)
Today’s products and services are so complicated and intertwined that their individual value creation is hard to determine. It is especially true when the products and services are necessary complements of each other and when they are affecting customer satisfaction for a long time. In the case of durable products needing professional installment service, the study of value creation poses many difficulties. Our research shows and emphasizes the process characteristic of value creation, and how the different steps (production, service, long-term use) should be looked at, and what further analyses can be done.